The effect of environmental enrichment on behaviour, production parameters and meat quality of finishing lambs in a feedlot - Liebenberg, Mariska (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.